Barriers to healthcare access: a multilevel analysis of individual- and community-level factors affecting female youths’ access to healthcare services in Senegal - Hailu Aragie; Habtu Kifle Negash; Mihret Getnet; Winta Tesfaye; Yibeltal Yismaw Gela; Tseganesh Asefa; Maru Mandefro Woldeyes; Hiwot Tezera Endale (BMC Health Services Research)
Abstract Introduction Despite the importance of preventive and curative healthcare use, female youths show a lower likelihood of usage. Factors such as language barriers, autonomy, household economic status, residence, and the education levels of individuals and their spouses influence this dynamic, but with limited evidence from Senegal. Thus, this study explores the magnitude and factors influencing healthcare access among female youths in Senegal. Methods This study used data from the 2023 Senegal Demographic and Health Survey (weighted sample size = 7,107). Multilevel logistic regression was used to test both individual and community-level factors associated with the outcome variable, barriers to accessing healthcare services. Adjusted odds ratios (AORs) with 95% confidence intervals (95% CI) were calculated to identify significant associations. Result The overall prevalence of barriers to accessing healthcare services among female youths was 69.40%. After adjusting for other variables in the final model, it was found that female youths who had no formal education (AOR = 2.11), primary education (AOR = 1.98), secondary education (AOR = 1.54), no health insurance coverage (AOR = 1.42), lived in poor households (AOR = 2.77), unmarried (AOR = 1.47), or lived in communities with high poverty levels (AOR = 1.87) faced significantly greater barriers to accessing healthcare. Conclusion To improve healthcare access for female youth in Senegal, targeted strategies must prioritize advancing educational opportunities, fostering economic empowerment, and expanding health insurance coverage. Special emphasis should be placed on addressing the unique challenges faced by unmarried female youth through tailored support programs. Furthermore, community-wide interventions to reduce poverty and enhance overall socioeconomic conditions are essential for creating a sustainable and equitable healthcare environment.